Eksistensi Perjanjian Internasional di Era Global - Haris Kusumawardana (Faculty of Law, Universitas Wijayakusuma, 2021)
This study aims to determine and analyze the existence of international agreements in the era of globalization. This research is a descriptive normative juridical law research. The approach used is a qualitative approach. In international relations, many countries experience problems in carrying out their relationships. This makes the role of international treaties very important, in order to regulate various matters that become agreements between countries in carrying out relations with other countries. For this reason, the role of international agreements in the era of globalization is an important topic to discuss. It aims to measure how far the country's compliance in carrying out international agreements. The implementation of international treaties well by the countries involved is the goal of the establishment of the international agreement.